Modification and Matrix Extension of the Bio-Rad iQ-Check E. coli O157:H7, STEC VirX, and STEC SerO Test Kits for the Detection of Shiga Toxin–Producing Escherichia coli (STEC) and Escherichia coli O157 From a Single Enrichment: AOAC Performance Tested MethodSM 020801 AOAC Performance Tested MethodSM 121203. (29th January 2020) - Brooks, Dane; Bastin, Benjamin; Crowley, Erin; Agin, James; Clark, Mike; Tourniaire, Jean-Philippe; Pierre, Sophie; Quiring, Christophe; Salfinger, Yvonne; Ziemer, Wayne; Chen, Yi
Abstract: Background: The iQ-Check Real-Time PCR kits use PCR technology based on gene amplification and detection by a real-time PCR thermalcycler for the detection of target analytes in select food matrices. The iQ-Check E. coli O157:H7 [ Performance Tested Method SM (PTM) 020801] and STEC VirX and STEC SerO (combined PTM 121203) methods were previously validated for different matrices under different enrichment schemes. Objective: To modify the current iQ-Check E. coli O157:H7 Kit for the detection of Escherichia coli O157:H7 from 25 to 375 g for raw ground beef (17% fat), raw beef trim, and fresh spinach. In addition, a matrix extension was validated for iQ-Check E. coli O157:H7 for raw chicken breast without skin (25 g), raw chicken thigh with skin (25 g), mechanically separated chicken (25 g), and raw ground pork (25 g). The study also included the modification of the iQ-Check STEC VirX and SerO Kits for the detection of non-O157 Shiga toxin–producing E. coli (STEC) for raw ground beef (375 g), raw beef trim (375 g), and fresh spinach (375 g) from STEC Enrichment Broth to buffered peptone water (BPW). All tests were carried out at 8–22 h (10–22 h for fresh spinach). Methods: Ground beef, beef trim, and spinach were co-inoculated with E. coli O157:H7, non-O157 STECs, and Salmonella spp. and analyzed for E. coli O157:H7 and non-O157 STECs after an 8-22 h enrichment in BPW for the beef matrices and after a 10–22 h enrichment in BPW for spinach. The chicken matrices were inoculated with E. coli O157:H7 only and analyzed after an 8–22 h enrichment in BPW. The iQ-Check Free DNA Removal Solution workflow was utilized for all matrices. Confirmations at the 22 h time point and method comparisons were conducted with the appropriate reference method as outlined in the U.S. Food and Drug Administration Bacteriological Analytical Manual Chapter 4A or the U.S. Department of Agriculture Food Safety and Inspection Service Microbiology Laboratory Guidebook Chapters 5.09 and 5B.05. For the iQ-Check STEC VirX and STEC SerO Kits, inclusivity and exclusivity were also performed. Results: The two inclusivity and exclusivity evaluations indicated that the test methods can accurately detect the target analytes and correctly excluded nontarget organisms after 8 h of enrichment. In the method comparison study, the iQ-Check E. coli O157:H7 and STEC VirX and STEC SerO test kits demonstrated no statistically significant differences between candidate and reference method results or between presumptive and confirmed results for all food matrices analyzed and the two time points (8 or 10 and 22 h). Both time points produced the same results, with no discrepancies. Conclusions: The iQ-Check real-time PCR kits are effective methods for the detection of E. coli O157 and non-O157 STECs (both the virulence factors and the O groups) from raw ground beef, raw beef trim, and fresh spinach in 375 g samples enriched in BPW for 8–22 h (10–22 h for fresh spinach). In addition, the iQ-Check E. coli O157 Kit is effective in detecting E. coli O157 in 25 g samples of raw chicken breast without skin, raw chicken thigh with skin, mechanically separated chicken, and raw ground pork. The iQ-Check test kits allow the end user to pair enrichments for multiple target analytes, allowing the user to prepare a single enrichment and perform a single DNA extraction. The Free DNA Removal Solution removes free DNA from samples prior to PCR analysis, protecting DNA from intact and living cells. Highlights: The method modifications were granted based on the data collected.